Exploring novel horizons - Bacterial phytases and their potential applications - Yana Gocheva; Stephan Engibarov; Rumyana Eneva; Irina Lazarkevich; Simona Mitova; Ivanka Boyadzhieva (Novel Research in Microbiology Journal)
The aims of this review are to focus on updating the current knowledge regarding the diversity of bacterial phytases, their importance in increasing the availability of phosphorus and other nutrients necessary for the growth and development of various plants and animals, and their roles in maintaining environmental sustainability. Phytases, enzymes that catalyze the hydrolysis of phytic acid, play a major role in various biotechnological processes; especially in agriculture. Among the diverse sources of phytases as prokaryotic and eukaryotic organisms, bacterial phytases have gained considerable attention due to their specific characteristics, potentials for genetic manipulation, and various biotechnological and industrial applications. Aerobic and anaerobic bacteria with phytase activity have been isolated from diverse ecological niches, including soils, fermented foods, plant rhizospheres, and manure. Additionally, probiotic bacteria, essential for maintaining a healthy microbiota, have been shown to produce phytase, suggesting their potential applications in animal and plant growth, human nutrition, and food and feed industry.